KORUPSI DAN INTEGRITAS PUBLIK: Perspektif Nilai Budaya Bugis dan Al-Qur’an - Muhammad Yusuf (PILAR, 2013)
AbstractThis article suggests integration between prominent values of the Bugis culture and internalization of values of Islamic doctrine in protecting and preventing corruption. This paper gives us view about the urgency of values of local wisdom which are discovered from principle of values of culture of Bugis which are relevant with values of Islamic doctrine. There are two principle opinions which serve as basis for that. First, Indonesian people have various local cultures which otomatically bring about glorious values which very closed to their life. Second, Indonesian people are the largest population of muslims in the world, where populations more than 80% are muslims, so approach to Islamic doctrine that is a relevant. Unfortunately, base on statistics data, Indonesia naowdays always the most corrupt nations in the world, whereas the corruption contradicts values both their cultures and Islamic doctrine which the both teach honesty and integrity. And, the step must start from reformation and reorientation of education, that is based on the values.Key words: Corruption, local wisdom, Islam, Bugis, values.